Desain Pembelajaran Pendekatan Discovery Learning dengan Menerapkan Pembelajaran dari Finlandia - Cidi Cindiawati; Flavia Aurelia Hidajat (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to provide alternative solutions from learning using discovery learning approach learning design by applying learning from Finland. A learning design is used to create a learning model in this piece of literature. Students' requirements are taken into consideration throughout the development process. Discussed in depth, learning outcomes are tailored to the instructional goals. As a consequence of the findings of this research, educators who want to teach statistics using group data may consider adopting a method inspired by Finnish research and practice. This lesson is divided into small parts and starts from the basic understanding of statistics that students need.